2004
DOI: 10.1002/ejoc.200400194
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Continuous‐Flow System for Catalysis with Palladium(0) Particles

Abstract: Heterogeneous catalysis for organic synthesis under continuous‐flow conditions becomes possible by a new reactor‐based approach. Continuous‐flow reactors with a monolithic glass/polymer composite interior are loaded with palladium particles by ion exchange followed by reduction. When incorporated into a continuous‐flow setup (PASSflow) this reactor allows the transfer‐hydrogenation of alkenes, alkynes, nitro‐substituted aromatic compounds and benzyl ethers in the flow‐through mode. In addition, the activity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
75
0
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 126 publications
(77 citation statements)
references
References 99 publications
0
75
0
2
Order By: Relevance
“…Additionally, nanoconfinement of asymmetric catalysts in multiwalled carbon nanotubes was also accomplished [72,73]. Pd supported over 8 monoliths has been considered for continuous flow reactions [50,68,[74][75][76][77]. The comparison of homogeneous and heterogeneous paths for the ligandless Mizoroki-Heck reactions are also overviewed [78].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, nanoconfinement of asymmetric catalysts in multiwalled carbon nanotubes was also accomplished [72,73]. Pd supported over 8 monoliths has been considered for continuous flow reactions [50,68,[74][75][76][77]. The comparison of homogeneous and heterogeneous paths for the ligandless Mizoroki-Heck reactions are also overviewed [78].…”
Section: Methodsmentioning
confidence: 99%
“…A continuous flow microreactor was obtained from a monolithic glasspolymer composite [77]. An oxime-based palladacycle was immobilised onto polyvinylpyridine resin and it was loaded in a microreactor containing a monolithic composite material.…”
mentioning
confidence: 99%
“…[28] By taking advantage of ionic stabilization of palladium(0) particles [29] we demonstrated that these particles can be generated after reduction of palladate anions loaded on anion exchange resins [obtained by precipitation polymerization inside the void volume of megaporous glass [30] using chlormethylvinylbenzene (VBC) and divinylbenzene (DVB) as cross-linker]. [31] Beneficially, the deposition of palladium was carried out on the surface of this monolithic glass/polymer composite material inside a PASSflow reactor, a continuous flow system which was developed in our laboratories ( Figure 1). This reactor concept has the unique feature that it can be operated at a wide range of volumetric flow rates thereby reducing mass transfer phenomena.…”
Section: Introductionmentioning
confidence: 99%
“…The general procedure was modified from previous protocols for immobilising Pd within monolithic structures or on beads. [11,15,[18][19][20] The reactor system presented herein contrasts traditional polystyrene or silica solid sup-ports, which have a granular, bead or gel form, [7,[20][21][22][23][24] as it consists of multiple capillaries manufactured from ethylene-vinyl alcohol (EVOH). The capillary geometry provides a known flow profile, which can be easily characterised and modelled, and does not suffer from channelling problems that are typically observed in packed bed systems.…”
Section: Introductionmentioning
confidence: 99%